Pelatihan Penggunaan ‘Kahoot’ dalam Mengajar Reading Narrative bagi Siswa Kelas X SMA Veteran 1 Sukoharjo - Veronika Unun Pratiwi; Purwani Indri Astuti; Nurnaningsih Nurnaningsih; Arin Arianti; Mas Sulis Setiyono (Universitas Muhammadiyah Semarang, 2021)
During this pandemic, all sectors have collapsed, even the education sector, which is accustomed to face-to-face classes, has become mandatory for offline or online classes, so English teachers are also required to be more creative in developing learning media. Although English is a compulsory subject, the results attained from English subject are not very satisfying. Learning activities is one of the stages that determines the success of student learning. The quality of education and teaching can be enhanced by optimizing several elements such as students, teachers, learning indicators, lesson content, methods, media, and evaluation. Because of the importance of reading material for students, the Bangun Nusantara Sukoharjo Veteran University service team offers Kahoot application training for class X SMA Veteran 01 Sukoharjo. The method utilizsd in this method is a quiz that is taught to class X students according to the lesson plans and syllabus of class X students, as well as the reading material given. The target to be achieved from this service is to increase knowledge and instruction about reading training using Kahoot media for class X SMA Veteran 01 Sukoharjo. In addition, this dedication is expected to be able to achieve several things, nemely: (1) the teacher knows more about the ability of each student in reading comprehension; (2) teachers can think logically and systematically by utilizing existing media in answering quizzes through reading training; (3) students are assisted in learning to think from a point of view in thinking practice; (4) teachers can further develop students' motivation to learn; and (5) students are actively involved in class planning and management.